Critical Stylistic Analysis of Naming and Describing of Selected Media News - Adai, Salih Mahdi; Kareem, Thamir Muhammad (RIRAI Publisher, 2025)
This study employs Jeffries’ (2010) critical stylistics framework, focusing on the linguistic tool of